Musa spp. Germplasm Management: Microsatellite Fingerprinting of USDA–ARS National Plant Germplasm System Collection. Issue 5 (1st September 2014) - Irish, Brian M.; Cuevas, Hugo E.; Simpson, Sheron A.; Scheffler, Brian E.; Sardos, Julie; Ploetz, Randy; Goenaga, Ricardo
ABSTRACT: The USDA–ARS Tropical Agriculture Research Station (TARS) is responsible for conserving germplasm of a number of important agricultural crop species. Its banana ( Musa spp.) collection is comprised of diploid, triploid, and tetraploid accessions of cultivated, ornamental, wild, and synthetic hybrid accessions. To estimate genetic diversity, identify gaps, determine integrity, and generate clonal reference multilocus DNA profiles for a total of 175 accessions in the collection, a set of 22 microsatellite markers developed in the framework of the Generation Challenge Program (www.generationcp.org/, accessed 30 June 2014) by Centre de Coopération Internationale en Recherche Agronomique pour le Développement and recommended by the Global Musa Genomics Consortium were screened with an additional 15 reference DNA samples. Twenty‐one of the 22 microsatellite markers amplified well and generated a total of 302 alleles with an average number of 14.4 alleles per locus. In general, profiles were reproducible and consistent for the 21 loci when clonal field and tissue culture plants were compared with reference samples. The average number of alleles and gene diversity estimates demonstrated substantial genetic diversity in the collection. Principal coordinate and cluster analyses grouped accessions in the collection according to their ploidy level and genomic compositions. Markers that were used in the study distinguished accessions to the subgroup level and identified mislabeled accessions, notably in the tissue culture collection where phenotypic differences are difficult to observe. The accessions and fingerprint profiles for the TARS collection are available through the USDA National Plant Germplasm System, Germplasm Resource Information Network (GRIN‐Global) database www.ars‐grin.gov/ (accessed 30 June 2014).